Toward transparency of hybrid open access through publisher‐provided metadata: An article‐level study of Elsevier. - Jahn, Najko; Matthias, Lisa; Laakso, Mikael (Journal of the Association for Information Science & Technology, 2022)
With the growth of open access (OA), the financial flows in scholarly journal publishing have become increasingly complex, but comprehensive data on and transparency of these flows are still lacking. The opacity is especially concerning for hybrid OA, where subscription‐based journals publish individual articles as OA if an optional fee is paid. This study addresses the lack of transparency by leveraging Elsevier article metadata and provides the first publisher‐level study of hybrid OA uptake and invoicing. Our results show that Elsevier's hybrid OA uptake has grown steadily but slowly from 2015 to 2019, doubling the number of hybrid OA articles published per year and increasing the share of OA articles in Elsevier's hybrid journals from 2.6 to 3.7% of all articles. Further, we find that most hybrid OA articles were invoiced directly to authors, followed by articles invoiced through agreements with research funders, institutions, or consortia, with only a few funding bodies driving hybrid OA uptake. As such, our findings point to the role of publishing agreements and OA policies in hybrid OA publishing. Our results further demonstrate the value of publisher‐provided metadata to improve the transparency in scholarly publishing.